2022
DOI: 10.5812/jjm.122090
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Multiple Respiratory Viruses Among SARS-CoV-2-Positive and Negative Patients by Multiplex TaqMan One-Step Real-Time PCR

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has clinical manifestations similar to other common respiratory viral infections. There are limited data on the frequency of viral respiratory coinfection among patients infected with SARS-CoV-2 in Iran. Objectives: This cross-sectional study investigated the prevalence of multiple respiratory viruses among SARS-CoV-2-positive and negative patients during the coronavirus disease 2019 (COVID-19) pandemic in Iran. Methods: We included oroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In line with our results, several studies reported a low rate of respiratory viral co-infections in COVID-19 patients. For example, Garcia-Vidal et al, Nowak et (8,9,15,(24)(25)(26)(27). Several reasons, such as viral interference in the established infection and competition among co-infecting viruses, as well as social distancing and wearing a mask in public and decreased circulation of other respiratory viruses, might lead to low rates of viral respiratory co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, several studies reported a low rate of respiratory viral co-infections in COVID-19 patients. For example, Garcia-Vidal et al, Nowak et (8,9,15,(24)(25)(26)(27). Several reasons, such as viral interference in the established infection and competition among co-infecting viruses, as well as social distancing and wearing a mask in public and decreased circulation of other respiratory viruses, might lead to low rates of viral respiratory co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…In a primary study conducted in Iran, using the HiTeq 17 Viro Respiratory pathogen One‐Step RT‐PCR Kit (Genova, Bonda Faravar, Bioluence, Tehran, Iran), from December 2020 to March 2021, a total of 197 cases were studied: 106 of these cases were reported as SARS‐CoV‐2 negative and 91 were identified as positive. They reported the pathogens and the relevant percentages as HMPV (7.1%), HCoV‐NL63 (4.06%), Flu B (1.52%), HCoV‐HKU1 (1.52%), HRSV (2.03%), HPiV (1.01%), HAdV (1.01%), and HBoV (0.5%) 7 . Interestingly, Veisi et al 7 found Flu B in 1.52% of their cases and no case of Flu A.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the HiTeq 17 Viro Respiratory pathogen One‐Step RT‐PCR Kit (GeneovA), made in 2021 in Iran, was used in the present study; other studies have used this kit considering its appropriate sensitivity and specificity to identify various viral respiratory pathogens, including SARS‐CoV‐2, Flu A, Flu B, Flu A/H1N1, HCoV‐NL63, HCoV‐229E, HCoV‐HKU1, HCoV‐229E, HCoV‐OC43, HPiV‐1, ‐2, ‐3, HAdV, HBoV‐1, ‐2, ‐3, HMPV, and HRSV 7,26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations